(untitled) (Clinics, 2021)
OBJECTIVES: To describe the MORPHEOS (Morbidity in patients with uncontrolled HTN and OSA) trial, and describe the challenges imposed by the COVID-19 pandemic. METHODS: MORPHEOS is a multicenter (n=6) randomized controlled trial designed to evaluate the blood pressure (BP) lowering effects of treatment with continuous positive airway pressure (CPAP) or placebo (nasal strips) for 6 months in adult patients with uncontrolled hypertension (HTN) and moderate-to-severe obstructive sleep apnea (OSA). Patients using at least one antihypertensive medication were included. Uncontrolled HTN was confirmed by at least one abnormal parameter in the 24-hour ABPM and ≥80% medication adherence evaluated by pill counting after the run-in period. OSA was defined by an apnea-hypopnea index ≥15 events/hours. The co-primary endpoints are brachial BP (office and ambulatory BP monitoring, ABPM) and central BP. Secondary outcomes include hypertension-mediated organ damage (HMOD) to heart, aorta, eye, and kidney. We pre-specified several sub-studies from this investigation. Visits occur once a week in the first month and once a month thereafter. The programmed sample size was 176 patients but the pandemic prevented this final target. A post-hoc power analysis will be calculated from the final sample. ClinicalTrials.gov: NCT02270658. RESULTS: The first 100 patients are predominantly males (n=69), age: 52±10 years, body mass index: 32.7±3.9 kg/m2 with frequent co-morbidities. CONCLUSIONS: The MORPHEOS trial has a unique study design including a run-in period; pill counting, and detailed analysis of hypertension-mediated organ damage in patients with uncontrolled HTN that will allow clarification of the impact of OSA treatment with CPAP.